Land-use changes in Slovenian terraced landscapes - Drago Kladnik; Matjaž Geršič; Primož Pipan; Manca Volk Bahun (Acta Geographica Slovenica, 2019)
This article presents the findings of a study on long-term land-use changes in eight areas of various Slovenian landscapes. The emphasis is on comparing changes on terraced and non-terraced land from the early nineteenth century to the present and on a typological classification of land-use change, whereby a fifth type (i.e., extensification) is added to the established four types in Slovenia: afforestation, grass overgrowth, intensification, and urbanization. The article explains which factors have a decisive impact on land-use changes, especially in terms of abandoning terrace cultivation. The methodology used proves that there are important differences in the rate of land-use change between terraced and non-terraced land.